SAT0355 Inhibition of Human Aortic Endothelial IL-6 Levels by Candida Albicans Water-Soluble Fraction (CAWS). (15th July 2016) - Springer, J.M.; Smith, D.; Miura, N.; Ohno, N.; Maz, M.; Dileepan, K.
Abstract : Background: Serum interleukin-6 (IL-6) has been shown to closely follow disease activity in large vessel vasculitis 1 . Prior research by our group has demonstrated that mast cell degranulation downregulates lipopolysaccharide (LPS) induced aortic expression of IL-6 in vivo. This is accompanied by aortic upregulation of SOCS-1 2 . This effect is lost in histamine 1 receptor knockout mice suggesting that histamine is a primary mediator of aortic IL-6 inhibition. Prior studies have also demonstrated that mice injected with Candida albicans water-soluble fraction (CAWS) develop coronary and aortic arteritis 3 . The mechanism through which arteritis is induced by CAWS remains poorly understood. Objectives: The objective of this study is to determine the effects of histamine and CAWS on IL-6 production by human aortic endothelial cells (HAEC) in vitro. Methods: HAEC were cultured with histamine (10μM), LPS (100ng/mL), CAWS (10μg/mL), CAWS (1μg/mL) or a combination of these. After 22 hours, levels of IL-6 and 6-ketoprostaglandin-F1α, a breakdown product of prostacyclin, were measured. Microculture tetrazolium (MTT) assays were used to determine cell viability. Results: IL-6 levels were significantly lower in cells treated with CAWS 10μg/mL compared to controls (175.2±11.9 vs 270.0 pg/mL, p=0.006). Similarly, IL-6 levels were significantly lower with the addition 10μg/mL CAWS to LPS compared to LPS alone (359.8±37.74 vs 2906.5±318.02, p=0.0001). No significant differences were seen between the 10μg/mL and the 1μg/mL CAWS concentrations. Histamine synergistically enhanced IL-6 levels over LPS alone (3758.0±38.18 vs 2906.5±318.0, p=0.028). CAWS had no effect on prostacyclin levels compared to controls. MTT assays demonstrated no differences in cell viability in CAWS or histamine treated cells compared to controls. Conclusions: Our experiments suggest that CAWS inhibits IL-6 production in HAEC. Since IL-6 is a key cytokine in the development of large vessel vasculitis we suspect that endothelial cells do not play a role in CAWS mediated arteritis. Similarly, the inhibitory effects of histamine do not appear to be mediated through endothelial cells. Future research will focus on the in vivo effects of histamine on the development of CAWS mediated vasculitis. References: Weyand CM, Fulbright JW, Hunder GG, Evans JM, Goronzy JJ. Treatment of giant cell arteritis: interleukin-6 as a biologic marker of disease activity. Arthritis and rheumatism. May 2000;43(5):1041–1048. Springer J, Raveendran V., Smith D., Maz M., Dileepan K. Novel role of mast cells in the regulation of large vessel vasculitis. Paper presented at: European League Against Rheumatism 2014 meeting; June 12th, 2014, 2014; Paris, France. Nagi-Miura N, Shingo Y, Adachi Y, et al. Induction of coronary arteritis with administration of CAWS (Candida albicans water-soluble fraction) depending on mouse strains. Immunopharmacology and immunotoxicology. 2004;26(4):527–543. Acknowledgement: Supported by Basic Science Development Award from Department of Medicine at the University of Kansas. Disclosure of Interest: None declared